Efektivitas Pencampuran Ekstrak Daun Kelor (Moringa Oleifera) yang Difermentasi Menggunakan Aspergillus Niger pada Pakan Buatan Terhadap Laju Pertumbuhan Ikan Nila (Oreochromis Niloticus) - Pirmansyah Pirmansyah; Novita MZ; Arif Supendi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Tilapia (Oreochromis niloticus) is a freshwater fish that is in great demand by the public because it has a thick meat texture and an affordable price. The problems faced in aquaculture activities are the high cost of feed and the length of cultivation time. Feed is a vital component in aquaculture activities, therefore feed efficiency is needed to minimize production costs. The addition of fermented moringa leaf extract in pellets is expected to accelerate the growth period. This study aims to determine the effect of the addition of fermented moringa leaf extract on tilapia growth rate. This study used a complete randomized design (CRD) method with 4 treatments, namely the addition of moringa leaf extract to pellets with concentrations of 0%, 25%, 30%, 35%. The treatment was carried out for 28 days. Parameters observed in this study were fish growth including fish length, fish weight, survival rate (SR), food conversion rate (FCR) and water quality in the form of temperature, pH and DO. The data were analyzed using anova and SPSS application. The results showed that the addition of fermented moringa leaf extract with concentrations of 0%, 25%, 30% and 35% in tilapia (Oreochromis niloticus) feed for 28 days had a significant effect on tilapia growth.